The Influence of Workload and Performance Allowances on Employees Performance through Work Motivation - Kusnadi Kusnadi; Arthur Sitaniapessy; Rismawati Rismawati (Trescode Green Organization, 2025)
This study is to analyze the Influence of Workload and Performance Allowance on Performance Through Work Motivation of Employees of the Central Statistics Agency of West Nusa Tenggara Province. This study is descriptive with a quantitative approach. Samples were taken using the Statified Proportional Random Sampling technique, with a sample size of 170 respondents. The method of collecting data related to the research problem was carried out using the questionnaire method. The analysis in this study uses PLS (Part Least Square). The results of the study indicate that workload has a significant effect on work motivation, workload has an effect on employee performance, performance allowance has a significant effect on work motivation, performance allowance has a significant effect on employee performance, work motivation has an insignificant effect on employee performance, workload has an insignificant effect on employee performance through work motivation, performance allowance has an insignificant effect on performance through work motivation.